THE ROLE AND PROSPECTS OF THE NEW FOREIGN POLICY OF UZBEKISTAN IN THE SYSTEM OF INTERNATIONAL RELATIONS (Archive of Conferences, 2022)
Today Uzbekistan is entering a qualitatively new stage of its independent development. Along the way, he effectively cooperated with many countries and major international organizations in various fields. In particular, significant results are achieved in the development of friendly and mutually beneficial relations with foreign countries. Based on the comprehensive reforms carried out in our country in recent years, such priorities as improving the well-being of our people and increasing the prestige of New Uzbekistan in the eyes of the world community remain relevant.